Effect of submucosal dexamethasone injection on postoperative pain, oedema, and trismus following mandibular third molar surgery: a prospective, randomized, double-blind clinical trial. Issue 4 (April 2017) - Mojsa, I.M.; Pokrowiecki, R.; Lipczynski, K.; Czerwonka, D.; Szczeklik, K.; Zaleska, M.
Abstract: The aim of this study was to investigate the effect of the submucosal injection of 1 ml dexamethasone (4 mg/ml) on pain, swelling, and trismus following the extraction of retained lower third molars. Ninety patients (mean age 23.5 years) were split randomly into three equal study groups (30 patients in each): the 'before' group received dexamethasone 15 min before surgery and placebo 15 min after surgery; the 'after' group received placebo 15 min before surgery and dexamethasone 15 min after surgery; the 'placebo' group received placebo 15 min before surgery and placebo 15 min after surgery. Postoperative pain was recorded by the patients using a visual analogue scale, numerical rating scale, and the McGill Pain Questionnaire at 1, 2, 4, 6, 8, 12, and 24 h after surgery. The patients also recorded the total number of analgesic doses consumed during the 24 h after the procedure. Swelling (determined using linear measurements of the face) and trismus (determined through measurement of maximum mouth opening) were assessed at 48 h, 72 h, and 7 days following surgery. Better control of pain, swelling, and trismus was demonstrated for dexamethasone in comparison to placebo. Postoperative dexamethasone provided better pain control than preoperative dexamethasone. There was no difference in total rescue analgesic intake between the preoperative and postoperative dexamethasone groups.